The Transformative Vision : Reflection on the Nature and History of Human Expression by José A. Argüelles. - Argüelles, José A. (Boulder (Colorado) : Shambhala Publications Inc., 1975)
Bacon, Francis ; Blake, William ; Breton, André ; Brun, Charles Le ; Carrà, Carlo ; Clark, Kenneth ; Courbet, Gustave ; Cézanne, Paul ; Dali, Salvador ; Daumier, Honoré ; Degas, Edgar ; Delacroix, Eugène ; Delaunay, Robert ; Dubuffet, Jean ; Duchamp, Marcel ; Dürer, Albrecht ; Ernst, Max ; Gauguin, Paul ; Gericault, Théodore ; Goya, Francisco ; Hölderlin, Friedrich ; Kandinsky, Wassily ; Klee, Paul ; Klein, Yves ; Kupka, Frantisek ; LeSage, Augustin ; Lichtenstein, Roy ; Maeterlinck, Maurice ; Magritte, René ; Manet, Edouard ; Mathieu, Pierre ; Matisse, Henri ; Matta (Roberto Antonio Sebastian Matta Echaurren) ; Michelangelo ; Milton, John ; Mondriaan, Piet ; Monet, Claude ; Moore, Henry ; Munch, Edvard ; Müller, Max ; Nolde, Emile ; Picasso, Pablo ; Pissarro, Camille ; Pollock, Jackson ; Redon, Odilon ; Reinhardt, Ad ; Renoir, Pierre Auguste ; Rivera, Diego ; Turner, J.M.W. ; Warhol, Andy ; Wölfli, Adolf ; de Toulouse-Lautrec, Henri ; Van de Velde, Henry ; van Gogh, Vincent
Engels
boek